Challenges in the Microbiological Diagnosis of Implant-Associated Infections: A Summary of the Current Knowledge - Oliva, Alessandra; Miele, Maria Claudia; Al Ismail, Dania; Di Timoteo, Federica; De Angelis, Massimiliano; Rosa, Luigi; Cutone, Antimo; Venditti, Mario; Mascellino, Maria Teresa; Valenti, Piera; Mastroianni, Claudio Maria (Frontiers in Microbiology, 2021)
Implant-associated infections are characterized by microbial biofilm formation on implant surface, which renders the microbiological diagnosis challenging and requires, in the majority of cases, a complete device removal along with a prolonged antimicrobial therapy. Traditional cultures have shown unsatisfactory sensitivity and a significant advance in the field has been represented by both the application of the sonication technique for the detachment of live bacteria from biofilm and the implementation of metabolic and molecular assays. However, despite the recent progresses in the microbiological diagnosis have considerably reduced the rate of culture-negative infections, still their reported incidence is not negligible. Overall, several culture- and non-culture based methods have been developed for diagnosis optimization, which mostly relies on pre-operative and intra-operative (i.e. removed implants and surrounding tissues) samples. This review outlines the principal culture- and non-culture based methods for the diagnosis of the causative agents of implant-associated infections and gives an overview on their application in the clinical practice. Furthermore, advantages and disadvantages of each method are described.